Pengaruh Kompetensi Dan Independensi Auditor Terhadap Kualitas Dan Kinerja External Auditor Pada Kantor Akuntan Publik Di Indonesia Sebagai Jasa Pelayanan Kepada Masyarakat - Ratih Andaningsih (Fakultas Ekonomi Universitas Borobudur, 2016)
The auditor’s quality control influences mental competency and independence of external auditor like public accountant with independence auditor’s respondence. The audit quality control is a part of framework fenomena of external auditor in connections with incompetently and it does not independently and uncollectible just for detections of fraud in financial statements. (Eunike,2007 in Christiawan,2002). In this research , (Otley theory , 1980), sentral issue are Empiris evidence, as follows auditor independence as intervening variable will be mediations influences competency mental attitude and auditor’s external of the auditor’s quality control. The research method use exsplanatory in connections with two variable or more than two variable, and one variable is follow by other variable effect (Cooper and Schindler ,2006:143), with quantitative approaching method.The populations are external auditor which working in public accountant of Indonesia as follows Directory of Public accountant 2015 by IAPI.Sample of research 100 auditors in 5 (Five)Public Accountant in Bekasi and Jakarta area. The result of research had Competency Mental and Independence of auditor influence significance of the auditor’s quality control and ethical code of Accountant.Key Words: Competency , Independence, Mental attitude,Quality control, Ethical Code .